Youth and Indigenous Language: Assessing Javanese Krama Madya Language Vitality - Munawwir Hadiwijaya; Kingkin Puput Kinanti; Ike Dian Puspitasari (Universitas Pendidikan Ganesha, 2022)
The younger generation is one of the elements of society that is expected to maintain regional languages amid the development of globalization since they are the portrait of the cultural future. This study aims to measure the level of vitality of the Krama Madya language from the perspective of the young Javanese generation in Malang. The measurement framework used in this study is adopted from UNESCO language vitality measurement factors. Data were obtained from 100 young Javanese generations aged 17-27 years who live in Malang City with various backgrounds using the cluster random sampling technique, ranging from students, teachers, government agencies, and employees to traders, by distributing questionnaires, interviews, and direct observations in the field. The data were analyzed using a qualitative descriptive analysis framework adopted from Miles and Huberman (1994). This study indicates that Javanese Krama Madya among the young Javanese generation, based on nine factors of language vitality to measure the level of UNESCO language vitality, is categorized as vulnerable. The indication of this conclusion is based on the diminishing number of language transmissions between generations; the unavailability of literacy that supports the teaching of the language; as well as the negative attitude of the younger Javanese generation, as shown by the shift in the use of this variety with Indonesian and foreign languages in interactions with older and respected speech partners to show their politeness.